Professional Backgrounds in State Legislatures, 1993–2012. (September 2019) - Makse, Todd
In this paper, I introduce a new dataset of individual-level professional background data for state legislators in 98 chambers from 1993 to 2012. Using this data, I examine trends in the professional backgrounds of state legislators over the period of the study, with attention to institutional factors such as professionalism and legislative turnover and individual-level factors such as political party and gender. In addition, I briefly illustrate three applications of the data. First, I analyze the extent to which district-level demographic and political factors affect the probability that a district will elect a legislator from certain backgrounds. Second, I examine the relationship between occupational background and ideology, identifying the backgrounds that identify moderate and extreme members in each party. Third, I contrast the occupational backgrounds of legislators who hold leadership positions with the membership at large. Taken together, these examples speak to some of the ways in which the composition of state legislatures can reveal interesting and relevant information underlying legislative behavior and institutions.